Pre-service teachers’ views and their multi-criterion noticing: a vignette-based study - Kuntze, Sebastian; Schall, Katrin; Krummenauer, Jens (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
Mathematics teachers’ noticing is a key part of their professional competence. The complexity of the mathematics classroom often requires noticing with respect of multiple analysis criteria. Such multi-criterion noticing can be expected to depend on teachers’ views, as views might mediate teachers’ awareness of criteria and, consequently, their noticing related to these criteria. Despite its high relevance for classroom practice and instruction-related decision-making, research into the role of such views for multi-criterion noticing is scarce. This study consequently explores such interdependencies by a reanalysis of a data set from a study with 32 pre-service teachers who had been asked to analyse classroom cartoon vignettes. In order to elicit multi-criterion noticing, these vignettes had been designed to contain noticing needs related to different criteria. The pre-service teachers’ answers were coded according to whether evidence of criteria-related noticing could be found. In order to explore interdependencies with teachers’ views, an additional interpretive analysis was carried out, which yielded codes for evidence of teachers’ instruction-related views. The findings suggest that teachers’ prescriptive views on what should happen in the mathematics classroom often led to relatively superficial positive evaluations of situation aspects and blocked a deepened knowledge-based analysis of these situation aspects. The findings call for the design of learning opportunities which address and challenge such prescriptive views in order to foster mathematics teachers’ development in multi-criterion noticing. Vignette-based opportunities of profession-related learning can provide a pathway towards this goal.